Pelatihan Literasi Digital untuk Siswa- Siswi Madrasah Tsanawiyah (MTs) Darul Kholili Jember - Cholimatus Zuhro; Agus Setia Budi; Alfi Hidayatu Miqawati; Fitri Wijayanti; Nila Susanti (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
The digital literacy level of the Indonesian young generation is still low. Therefore, the students need to be equipped for digital literacy from an early age. This community service activity aims to increase the knowledge and skills of the students of Madrasah Tsanawiyah (MTs) Darul Kholili Jember. In this basic digital literacy training, the presenter used several mixed approaches, they are lecturing, discussion, and practice. The materials taught in this training include Digital Literacy, Digital Culture, Digital Ethics, Media Sosial Education and Cyber Bullying. After delivering the material, the presenter opened a discussion and question answer session, the participants were asked to practice the material that had been discussed. During the training, participants were very enthusiastic also active in discussion sessions and asked questions. It is hoped that this activity will contribute to the development of participants’ digital literacy. The result of this training activities showed that the students of Madrasah Tsanawiyah (MTs) Darul Kholili Jember have a good knowledge improvement in their digital literacy, however in the process of literacy digital training there were still some things that must be improved.